A solitary fibrous tumor/hemangiopericytoma of the fourth ventricle: case report and literature review. Issue 12 (December 2019) - Yang, Han; Zhang, Yuxin; Zheng, Ting; Li, Cao; Tang, Guangcai; Chen, Guangxiang
Solitary fibrous tumors/hemangiopericytomas (SFTs/HPCs) are rare in the central nervous system and intraventricular SFTs/HPCs are even rarer. We present a clinical case of SFT/HPC that was located in the fourth ventricle and performed a literature review of radiological findings of SFT/HPC. The patient was a 52-year-old man who presented to our hospital with dizziness and progressive weakness in his left extremities. Computed tomography and magnetic resonance imaging showed an irregular-shaped mass in the fourth ventricle. The upper anterior and lower posterior parts of the mass showed different densities and signal intensities, which formed a black and white sign. The upper anterior and lower posterior parts of the mass were enhanced to different degrees, and showed heterogeneous reversed enhancement. The patient underwent surgical resection and the mass was histologically confirmed to be an SFT/HPC. SFTs/HPCs of the fourth ventricle are rare, but show characteristic radiological presentations. In the present case, we observed a solid mass with flow voids, black and white sign, and heterogeneously reversed enhancement in the fourth ventricle. Collectively, these radiological features suggested the diagnosis of SFT/HPC.